2015
DOI: 10.1016/j.tvjl.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of tyrosine kinases and use of imatinib in small animal practice

Abstract: Imatinib inhibits the activity of several tyrosine kinases, including BCR-ABL, KIT and platelet-derived growth factor receptor (PDGFR). Dysregulation of KIT is found in mast cell tumours (MCTs) and KIT is mutated in approximately 30% and 70% of canine and feline MCTs, respectively. KIT mutations have also been reported in canine and feline gastrointestinal stromal tumours (GISTs), canine acute myeloid leukaemia and canine melanoma. In addition, BCR-ABL and PDGFR mutations have been found in canine leukaemia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 84 publications
(95 reference statements)
0
49
0
4
Order By: Relevance
“…Moreover, other studies reported that several TKIs with different chemical structures from imatinib induced objective tumour regression in canine MCTs with these mutations Hahn et al 2008;London et al 2009). However, several studies reported that clinical activity of imatinib against MCT could not be predicted based on the presence of mutations in exon 8 or 11 of c-kit (Isotani et al 2008;Bonkobara 2015) as in the cases described here.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, other studies reported that several TKIs with different chemical structures from imatinib induced objective tumour regression in canine MCTs with these mutations Hahn et al 2008;London et al 2009). However, several studies reported that clinical activity of imatinib against MCT could not be predicted based on the presence of mutations in exon 8 or 11 of c-kit (Isotani et al 2008;Bonkobara 2015) as in the cases described here.…”
Section: Discussionmentioning
confidence: 59%
“…In addition to these mutations, several minor mutations (allele frequencies 0.7%‐3.7%) also were identified: c.2579A>G (in exon 18) in all cell lines; c.2513A>G (in exon 18) in parental line VI‐MC and the cVI‐MC1 and trVI‐MC1 sublines; and c.2418G>T (in exon 17), c.2515A>G (in exon 18), and c.2579A>T (in exon 18) in cVI‐MC1 only. No mutation in KIT exon 11, where the mutation is most frequently found in canine MCT (Bonkobara, ), was identified. All of the mutations identified by NGS were missense mutations (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…were analyzed by NGS (Table 1) (Bonkobara, 2015), was identified. All of the mutations identified by NGS were missense mutations (Table 1).…”
Section: Genetic Alterations Of Kit In Vi-mc During Clonal Expansiomentioning
confidence: 99%
“…In general, it is difficult to use humanized antibody drugs in dogs because of failure of cross‐reactivity . Alternatively, small‐molecule drugs often cross‐react with various species . As EGFR protein overexpression is also observed in 72% of canine TCC, the HER2 and EGFR tyrosine kinase inhibitor lapatinib may be effective in canine TCC.…”
Section: Introductionmentioning
confidence: 99%